Ibn Taymiyyah's View on Waqf Development and How It’s Application in University Development in Indonesia - Muhammad Azrul Amirullah; Fadhila Tianti Mudi Awalia; Saipul Nasution; Fazari Zul Hasmi Kanggas (ZISWAF ASFA, 2026)
This study examines Ibn Taymiyyah’s perspective on waqf development and its application in university development in Indonesia. Using a descriptive qualitative method and content analysis approach, this research analyzes classical Islamic legal thought, contemporary waqf practices, and the implementation of waqf-based funding in several Indonesian Islamic universities. The findings show that Ibn Taymiyyah viewed waqf as a flexible and productive instrument aimed at maximizing public benefit (maṣlaḥah). He permitted the exchange, sale, or redevelopment of unproductive waqf assets when such actions generated greater social and educational benefits. This principle is highly relevant to the contemporary context of higher education financing in Indonesia, where universities increasingly require sustainable and independent funding sources. The study identifies four major forms of waqf development based on Ibn Taymiyyah’s thought: utilization of waqf proceeds, istibdal of unproductive assets, investment flexibility, and land financing. Several Indonesian universities have implemented these principles through productive waqf management, infrastructure development, scholarship programs, and educational investment schemes. This study argues that waqf can function not only as a religious instrument but also as a sustainable financial model for strengthening higher education development in Indonesia.